Philippines : Country Water Resources Assistance Strategy 2003 - World Bank (Washington, DC, 2013)
The Water Resources Sector Strategy (WRSS) supports implementation of the Bank's 1993 Water Resources Management Policy, using the experience updated internationally, with water resources and management. This country Water Resources Assistance Strategy (CWRAS) identifies the Philippines principal water resource challenges, the current situation, how the Bank is assisting at present, and what it should in the future. In summary this strategy can be summarized as follows: 1) Bank assistance should translate the rhetoric of water conservation, and sustainability, into practical-realistic programs, and policies; 2) focus should be on promoting cooperation of local government units (LGUs), and water users themselves, and, on following a "bottom-up and top-down" approach, that includes active participation of water users, in addition to developing infrastructure, and management into water resources projects; 3) water resource management (WRM) initiatives should respect cultural practices, which have evolved to provide sustainable WRM in a micro-watershed context. Indigenous water systems provide clues to how WRM should be rooted in the socio-cultural context; and, 4) prioritize support for the use of economic instruments in managing river basins, facilitating private sector participation I the water supply and sanitation sector, and supporting the decentralization of responsibilities for WRM.